(untitled) (CIPEEX, 2025)
The phenomenon of population aging is a global reality, marking a significant demographic transition in many societies. This phenomenon brings with it specific challenges and needs, especially regarding health, well-being, and the Quality of Life of the elderly. This study aimed to investigate the perception of Quality of Life among elderly people residing in a Long-Term Care Institution. A quantitative approach was adopted for the research, encompassing a sample of 24 elderly people. The results showed that sensory functioning was the best-evaluated facet, with 73.96%, while autonomy presented the lowest score, with 38.54%, indicating serious limitations in this aspect. The global analysis revealed a moderate QoL, with an average of 59.98%, suggesting the need for interventions aimed at improving the autonomy and participation of those involved in the research. It is concluded that there is significant potential to enhance the quality of life of the elderly in the institution, especially in areas of greater vulnerability, reinforcing the importance of adequate public policies and intervention strategies.